Analisis Penguatan Karakter Siswa Muslim di Sekolah Dasar Minoritas Melalui Pendidikan Agama Islam - Soedjiwo, Novena Ade Fredyarini (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
This study aims to strengthen the character of Muslim students in public elementary schools in Denpasar Bali through Islamic religious education, especially faith and morals and to analyze teaching materials in strengthening character in the material